INVESTIGATING STUDENTS’ MATHEMATICAL LITERACY PERFORMANCE IN PISA QUESTIONS: INFORMATION PROCESSING THEORY - SITI MUFIDAH, SUDIRMAN, MAKBUL MUKSAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The theory of information processing examines how individuals process information in their minds, which is essential for students in solving problems, including PISA tasks. This study explores students' mathematical performance in solving PISA tasks through the lens of information processing theory. A qualitative approach was employed, involving three research subjects with varying levels of mathematical literacy: level 2 (low), level 3 (medium), and level 5 (high). Data were collected through task analysis and semi-structured interviews. Data analysis involved data reduction to filter relevant information, narrative presentation of findings, and conclusion drawing. The study adopted the Atkinson-Shiffrin information processing model, which comprises sensory register, working (short-term) memory, and long-term memory. Cognitive processes analyzed included attention, perception, rehearsal, retrieval, and coding. The findings revealed that cognitive processes occurred at all levels, but their effectiveness varied by task complexity. Level 2 students exhibited cognitive processes primarily in problems characterized by the use of basic arithmetic calculations. The cognitive difficulties encountered by these students occurred during the attention phase, where they struggled to comprehend problems involving models, resulting in errors during the encoding process. Level 3 students demonstrated cognitive processing in problems characterized by the use of explicit models. Cognitive challenges included issues in the attention phase, as students had difficulty understanding problems with complex characteristics, disruptions in the perception phase, where they experienced cognitive lapses in concept application, and errors in rehearsal, where repeated responses with inconsistent calculations led to misunderstandings in the encoding process. Level 5 students engaged in cognitive processing for problems of higher complexity. These students' memory effectively retained the information necessary for processing, enabling them to recall concepts with clarity and precision. These findings imply the need for collaborative learning in classrooms to address diverse cognitive abilities, bridging differences, fostering interaction, and encouraging peer support. Teachers can design collaborative activities to facilitate and enhance students’ problem-solving skills effectively.